Preservation watch: what to monitor and how - Becker, Christoph (2012)
For successful preservation operations, a preservation system needs to be capable of monitoring compliance of preservation operations to specifications, alignment of these operations with the organisation’s preservation objectives, and associ- ated risks and opportunities. This requires linking a number of diverse information sources and specifying complex con- ditions. For example, the content to be preserved needs to be related to specifications of significant properties, to the file formats used to represent that content, to the software environments available to analyse, render and convert it and the technical environments available to the designated user communities that will consume this content. This article analyses aspects of interest in a preservation context that call for automated monitoring and investigates the feasibility of drawing sufficient information from diverse sources together and linking it in a meaningful way. We define a number of preservation triggers that lead to preservation planning activities and present the requirements and a high-level design of a preservation watch system that is currently being developed. We demonstrate the value of such a monitoring approach on a number of scenarios and cases.